Factors affecting the level of financial report publication by BAZNAS and LAZ organizations throughout Indonesia - Ahmad, Nur Fadilah; Furqan, Andi Chairil; Andriana, Cindy (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to present the factors influencing the publication of financial reports by the National Amil Zakat Agency (BAZNAS) and Zakat Amil Institutions (LAZ) throughout Indonesia. The research utilizes secondary data from BAZNAS and LAZ across Indonesia from 2018 to 2022, with a final sample size of 2,166 observations. The results of this study indicate that the age of the institution, institutional status, and institutional type contribute to the level of financial report publication by BAZNAS and LAZ. This research implies the need for increased transparency and accountability to enhance the level of financial report publication, thereby improving the reputation and public trust in these institutions. Subsequent researchers are encouraged to conduct more in-depth analyses of the financial aspects published by BAZNAS and LAZ.